THE IMPACT OF ACADEMIC TUTORING EXPERIENCE ON TEACHING CAREER IN MEDICAL SCHOOL (CIPEEX, 2025)
Academic tutoring is a fundamental pillar of higher education, providing pedagogical support and developing essential skills for a teaching career. However, there is a lack of in-depth research on its role as an initiation into teaching, and a perception of low interest in the teaching profession during undergraduate studies. This study aimed to analyze the impact of academic tutoring on professional development, exploring its contribution to awakening and consolidating interest in university-level teaching. The methodology used was a systematic literature review, following PRISMA guidelines, with searches in databases using clear inclusion and exclusion criteria. The results show that tutoring is a privileged space for developing teaching skills through giving classes, exposure to active learning methodologies, and the opportunity to improve communication and develop the autonomy and decision-making capacity that are crucial for teaching. This experience also deepens the tutors' knowledge, solidifying their learning and enriching their resumes. Furthermore, it contributes pedagogically through direct peer-to-peer support, creating a rich learning environment for all students. Despite the benefits, there are significant challenges, such as the scarcity of research, the perception of low interest in teaching during undergraduate studies, the mistaken view of tutoring as an administrative task, a lack of clear regulation, and the unequal distribution of scholarships. The study concludes that academic tutoring contributes significantly to professional development, especially for a teaching career, by improving unique skills. It is an indispensable activity, but the existing obstacles must be highlighted, discussed, and overcome to properly value the work of academic tutors.
Keywords: Mentoring; Teaching; Professional Training